Perbandingan Sumber Pendapatan Negara Menurut Perspektif Abu Ubaid dan Sistem APBN Indonesia - Ali Akhmadi (Penerbit Jurnal Indonesia, 2026)
This study investigates the comparative dynamics of state revenue sources between Abu Ubaid’s Kitab al-Amwal and the Indonesian State Budget (APBN) framework. Utilizing a qualitative library research design with a descriptive-comparative approach and content analysis, the research delineates the structural evolution of fiscal justice from classical paradigms to contemporary regulations. The findings reveal a profound philosophical convergence centered on maslahah (public interest), where the state serves as a fiduciary entity for the equitable redistribution of wealth. Technically, classical instruments such as kharaj and ushr demonstrate functional equivalence to Indonesia’s Land and Building Tax (PBB) and Customs. However, a distinct ontological divergence persists: Abu Ubaid’s model is anchored in a static, theocentric-ethical foundation, whereas the APBN operates within a dynamic, anthropocentric-technocratic constitutional structure. A pivotal insight of this study identifies Abu Ubaid’s mandate for